PENGARUH PENGUNGKAPAN EMISI KARBON, ECO- EFFIENCY, DAN GREEN INNOVATION TERHADAP NILAI PERUSAHAAN - Vincensa Fanda; S, Patricia Febrina Dwijayanti (JURNAL ILMIAH MAHASISWA AKUNTANSI, 2024)
The main purpose of a company is to maximize company value and create financial prosperity for company owners and interested parties. Basically, investors use company value as an indicator in assessing company performance. However, the reality is that the rapid development of the industry is also accompanied by increasing environmental problems, but many companies do not consider environmental impacts in their operational activities. In this context, it is important for companies to not only focus on economic aspects, but also consider environmental aspects in order to increase company value. There are several factors that can affect firm value. Therefore, this study was conducted with the aim of examining the disclosure of carbon emissions, eco-efficiency, and green innovation on firm value. This research is quantitative research using hypothesis testing. The independent variables used in this study are disclosure of carbon emissions, eco-efficiency, and green innovation. The dependent variable is firm value. This study uses control variables of company size and profitability. The object of this research is all manufacturing sector companies listed on the IDX in 2019-2022. The analysis technique used in this research is multiple regression analysis. The results of this study prove that eco-efficiency and green innovation have a positive influence on firm value. This means that the more companies that implement eco-efficiency and green innovation will encourage an increase in firm value. On the other hand, carbon emission disclosure has no influence on firm value. This is because the level of disclosure made by the company is still low so that it has not been able to affect the firm value.